New records of four Odonata species of Community interest in central and southern Italy, with conservation notes - Novaga, Riccardo; Corso, Andrea; Romano, Antonio (Fragmenta entomologica, 2024)
This paper provides new data on the following four species of dragonflies and damselflies (Odonata Coenagrionidae, Gomphidae, Synthemistidae, Cordulegastridae), which contribute to updating their known distribution in central-southern Italy: Coenagrion castellani Roberts 1948, Lindenia tetraphylla (Vander Linden 1825), Oxygastra curtisii (Dale, 1834) and Cordulegaster trinacriae Waterston, 1976. These species are all included in Annexes II and IV of the Habitat Directive 92/43/EC. New sites of C. castellani and C. trinacriae were discovered in the Latium, Campania, Abruzzo and Molise regions, while the presence of O. curtisii was observed in Molise and southern Latium, after a 70-year absence of records. Lindenia tetraphylla was observed at two new sites in southern Apulia. The presence of populations morphologically attributable to C. trinacriae was confirmed in southern Latium, reaching at least the Liri river (FR). Some bibliographic sites of C. castellani, C. trinacriae and L. tetraphylla were also confi rmed. All the sites were listed and mapped, accompanied by brief data on habitat types and on their inclusion within Natura 2000 network sites. Information on persistent threats to these sites is provided, along with conservation notes.